DEFINED THEORETICAL AND METHODOLOGICAL PROBLEMS OF STUDYING THE STRUCTURE OF THE NATIONAL MENTALITY (Journal of actual problems of jurisprudence, 2019)
At modern period of the building democratic and legal state of necessary consideration determined theoretical andmethodological problems of the study of the construction national менталитета for the reason determinations of the nationalconsciousness Kazakhstan society.